PROBLEMATIKA LEARNING LOSS KEDISIPLINAN BELAJAR DI SDN BOGAK TAHUN PELAJARAN 2026/2027 - Suryajaya; Lalu Andi Fathullah, Andi; Mardiana; Basilius Redan Werang, Basilius (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to describe learning loss reflected in students’ learning discipline at SDN Bogak during the 2026/2027 academic year, identify its contributing factors and impacts, and explain recovery efforts undertaken by the school and families. A descriptive qualitative approach was used. Data were collected through observation, semi-structured interviews, and documentation involving the principal, classroom teachers, students, and parents or guardians selected purposively. Data were analyzed through data condensation, data display, and conclusion drawing, while trustworthiness was examined through source and technique triangulation. The findings show that 10 students submitted assignments after the agreed deadline. Teachers associated this condition with limited parental support and supervision, whereas parents reported that children tended to prioritize play and disregard instructions to complete assignments. Delayed submissions reduced students’ opportunities to receive timely feedback and increased the risk of falling behind subsequent learning activities. School–family discussions produced an initial improvement, with some students beginning to submit assignments more promptly. Continuous monitoring and consistent cooperation between the school and families are therefore needed to strengthen learning discipline.